Dolphin Junction : stories - Herron, Mick (New York, NY : Soho Crime, 2021)
"In Dolphin Junction, devoted fans and future converts alike will find much to amuse, delight, and terrify them. Five standalone nerve wrackingly thrilling crime fiction stories are complemented by four mystery stories featuring the Oxford wife-and-husband detective team of shrewd Zoe Boehm and hapless Joe Silvermann. The collection also includes a peek into the past of Jackson Lamb, irascible top agent at Slough House"--
Booklist
Publishers Weekly
Kirkus Reviews
Booklist Starred Reviews
Keywords: Short stories; Detective and mystery stories, American; Detective and mystery stories; Mystery fiction